Reconstruction of the National Legal System: Study the Implementation of the Maqâsid al-Shari‘ah Theory - Faidi, Achmad (al-'adalah, 2018)
This paper discusses the implementation of the theory of maqâsid al-shari‘ah in the formation of a national legal system in Indonesia. Colonialism in the past has made national law covered with the nuance of European Continental legal system which is not compatible with the character of the national culture. The awareness to reconstruct the national legal system has echoed since the 1998 reform, but until now it has not found the right construction formula. This article offers the theory of maqâsid al-shari‘ah as one of the tools in an effort to reconstruct the national legal system. Based on author analysis, the concept of maqâsid al-shari‘ah is suitable to be applied because it adopts the noble values contained in the national ideology of Pancasila as well as the legal principles that exist in Islam as a religion of the majority of the population of this country